Transformation of Islamic Educational Institutions during the Umayyad Dynasty (661-750 AD): From Kuttab to a Structured Education System - Muhammad Dandi Alfariji (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
The Umayyah Dynasty (661-750 AD) was a crucial period in the history of Islamic civilization marked by the expansion of territory from China to Andalusia, thus giving rise to an urgent need for a more structured and institutional education system. Amidst cultural intersections with Persian, Byzantine, and Greek civilizations, Islamic Education during the Umayyad Dynasty identified the emerging institutional forms and explained the driving factors behind these developments. This study uses a historical-descriptive method with a literature review approach. The results of the study indicate that Islamic Education during this period developed through a diversification of institutions, starting from Kuttab as a primary education, mosques as centers of secondary and higher education, badiah as an institution for preserving Arabic, to Bimaristan as a center for medical studies and the Literature Council as a scientific and cultural forum. The Umayyad Dynasty was thus a period of Islamic intellectual incubation that laid a solid foundation for the golden age of the Abbasid era, while also offering inspiration for the development of integrative and multidisciplinary contemporary Islamic Education.